2018
DOI: 10.1016/j.jbtep.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement attenuation of intrusive social anxiety imagery: A pilot study

Abstract:  Eye movements (EMs) are applied to involuntary and intrusive social anxiety imagery  Images were lower in vividness after EMs than after a control task  EMs may prevent increases in intrusive image vividness following exposure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…According the literature single or combined usage of medical agents and cognitive behavioral therapies is the most common and effective method in treatment of SAD (Wild & Clark 2011). Recent research has shown that negative, intrusive mental imagery plays a prevalent and causal role in SAD (Homer & Deeprose 2018). In a study conducted in Turkey found average LSAS scores associated with childhood trauma experience among patients with SAD (Belli et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According the literature single or combined usage of medical agents and cognitive behavioral therapies is the most common and effective method in treatment of SAD (Wild & Clark 2011). Recent research has shown that negative, intrusive mental imagery plays a prevalent and causal role in SAD (Homer & Deeprose 2018). In a study conducted in Turkey found average LSAS scores associated with childhood trauma experience among patients with SAD (Belli et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a couple of interventions (mainly imagery with competing tasks), asked for any intrusive social imagery or specifically for prospective (flashforward) imagery. This is of interest as previous findings have shown that these forms of negative imagery appear prevalent and relevant as well in social anxiety (e.g., Ashbaugh, Fishman, and Houle‐Johnson 2019; Homer and Deeprose 2018; Thunnissen et al. 2022).…”
Section: Discussionmentioning
confidence: 88%
“…This gives rise to questions on the added value as well as the optimal timing of IR in current SAD treatment. Two other studies included a couple of minutes of imagery with an auditory task or IE with intrusive imagery that did not result in decreased imagery distress and vividness (while imagery with EM did result in decreased imagery distress and vividness; Homer, Deeprose, and Andrade 2016; Homer and Deeprose 2018). In the study that also assessed social anxiety as an outcome, the evaluated interventions (i.e., imagery with an auditory task and imagery with EM) did not result in decreased anxiety (Homer, Deeprose, and Andrade 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation